Developing HOTS-Based Critical Reading Textbook for Junior High Schools in Ngabang - Monika Widyastuti Surtikanti; Mustika Aji Hertanto; Antonius Setyawan Sugeng Nur Agung (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2020)
This study is a research and development under the issue of developing English textbook oriented to HOTS-Based Critical thinking for Junior High School Students especially for the seventh grade students in Ngabang, Landak, West Kalimantan. It is based on the evidence that the English teachers find difficulty in finding HOTS-based English textbook as one of the teaching tools. This issue is supported by the result of textbook evaluation. It reveals that most of the existing English textbooks used by the teachers still emphasizing on remembering and understanding level. These preliminary data led the researchers to develop HOTS-Based Critical Reading Textbook for the seventh grade students. The objectives of this study are to describe the materials needed by both teachers and students and to develop “Critical English”, the English textbook with HOTS and critical reading as the basis. In developing “Critical English” textbook, the researchers employed 7 stages of Research and Development study suggested by Borg and Gall (1983) namely need analysis, textbook evaluation, designing product specification, developing the product, expert validation, revision, try-out, and finalization. This study involved 2 English teachers and 20 (twenty) students of the seventh grade at SMP Negeri 2 Ngabang. The data were obtained through questionnaire, interview, classroom observation, expert judgment sheet, documents analysis, and focus group discussion. Then, the gathered data were analysed using a descriptive qualitative method. The research findings reveal that “Critical English” textbook facilitate the teachers to build the students’ critical thinking and the materials provided in the textbook trigger the students to develop their creativity and critical thinking so that the teaching and learning process can be more active and interesting.